Algorithm for Calculating Flowrate of Fluid Energy Carrier for Flowmeter Based on Standard Long Radius Nozzle - Leonid Lesovoy; Fedir Matiko; Iryna Maidanovych (Energy Engineering and Control Systems)
New equation and algorithm are developed for non-iterative calculating flowrate of fluid energy carrier for pressure differential flowmeter based on long radius nozzle. This equation implicitly contains three build-in iterative cycles for calculating flowrate. According to the results of comparing the flowrate values obtained by developed non-iterative algorithm to the flowrate values by standard iterative algorithm, the authors found that the developed non-iterative algorithm ensures the accuracy of flowrate calculation specified by the requirements of DSTU GOST 8.586.5:2009. Therefore, the proposed equation and algorithm for calculating flowrate can be used for flowmeters based on standard long radius nozzle for both technological and commercial metering flowrate of fluid energy carriers. Application of the developed algorithm makes it possible to increase the speed of calculating flowrate of fluid energy carriers by means of microprocessor controllers.